328 THROMBOCYTOPENIC SYNDROMES MASQUERADING AS CHILDHOOD IMMUNE THROMBOCYTOPENIC PURPURA: A 10-YEAR REVIEW. Issue 1 (1st January 2007) - Bryant, N.; Watts, R.
Abstract : Immune thrombocytopenic purpura (ITP) is the most common cause of thrombocytopenia in children and adolescents. However, there are a number of other diagnoses that are often mistaken for ITP. A 10-year retrospective chart review (1993-2003) was performed at the Children's Hospital of Alabama to characterize ITP. Initially, 492 patients who had the coded diagnosis of ITP (ICD 287.3) were identified. However, 83 (17%) patients were found to have alternative diagnoses on chart review. Of the 83 patients, 13 patients represented coding errors or study classification errors. The 70 remaining patients had an alternative explanation for their thrombocytopenia, consisting of 31 different diagnoses. The most common diagnoses were familial thrombocytopenia (10%), systemic lupus erythematosus (SLE) (9%), hypersplenism (9%), neonatal alloimmune thrombocytopenia (7%), and Wiskott-Aldrich disease (7%). Sixteen of the patients (23%) were ultimately diagnosed with one of a number of congenital syndromes with concurrent thrombocytopenia. These included Wiskott-Aldrich, thrombocytopenia with absent radii, Hermansky-Pudlak syndrome, Fanconi's anemia, Klippel-Trenaunay-Weber syndrome, DiGeorge syndrome, and osteopetrosis. Ten patients (14%) were diagnosed with a rheumatologic/autoimmune disease (SLE, rheumatoid arthritis, Evan's syndrome, and Crohn's disease). Four patients (6%) had an infectious etiology (CMV, HIV, gram-negative septicemia). Six patients (9%) had disorders of impaired hematopoiesis or platelet segmentation (macrothrombocytopenia, May Hegglin anomaly, amegakaryocytic thrombocytopenia, and aplastic anemia). There were nine patients (13%) who had neonatal autoimmune thrombocytopenia. The alternative diagnoses were defined by history, physical examination, blood smear interpretation, and further diagnostic studies. Although our review confirms that most children with thrombocytopenia are diagnosed with ITP, fully 17% of our population in a tertiary care medical center manifested other diagnoses. The clinician evaluating a child with thrombocytopenia must keep an open mind about the possible diagnosis and perform a comprehensive evaluation to include careful physical examination, complete blood count with differential, review of the peripheral blood smear to evaluate for platelet size, morphology and leukocyte inclusions, and other directed laboratory studies based on the clinical picture. ITP must be a diagnosis of exclusion as misdiagnosis of ITP in a child with thrombocytopenia may have a significant impact on morbidity and mortality.